Blood Lymphocytes Detection in Iraqi Diabetic Type 2 Patients Infected with Chronic Toxoplasmosis by Using Flow Cytometry - Israa Kasim Al-Aubaidi1 , Sarah Ali Saeed1 , Ahmed Issa Jaaffar2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Toxoplasma gondii is an obligate parasite infects different species of mammals as intermediate hosts whileinfects number of family of cats as definitive hosts. It has three morphological types: tachyzoites, bradyzoitesand sporozoites. It causes (H.I.) humoral immunity and (C.M.I) cell mediated immunity response which ismeasured one of the most characteristic immunological types of this parasite infestation. Diabetes mellitus(DM) is considered as a heterogeneous group of metabolic abnormalities with hyperglycemia due either toa reduction of insulin biological function or absolute insulin deficiency. Researchers discovered that longterm infection with T. gondii may be dangerous agent for DM type 2, and there is no relation betweentoxoplasmosis and DM type 1. The aim of this study include detection of CD3 in Iraqi diabetic type 2infected with chronic toxoplasmosis by using flow cytometry. This study included 100 blood samples werecollected from Iraqi diabetic type 2 patients and 50 blood samples of healthy volunteers with age range(15-75) years and mean 49.9±12.8 from Al – Imam Ali general hospital during May 2018 until August inthe same year. Diagnose of toxoplasmosis infection was done by using rapid diagnosis test/ cassette and byToxo IgG antibodies immulite torch assay while diabetes diagnosis by fasting glucose tests in addition CD3were detected by using flow cytometric method. Diabetic patients a group infected with toxoplasmosis havethe highest level of blood blood sugar in comparison with other groups. Forty – five samples of diabetictype 2 infected with chronic toxoplasmosis by detection IgG antibody in highly level 106.2± 90.2 withhighly significant differences in comparisons with other groups ( diabetic patients 3.6± 1.2 and control group4.0±0.6 ) while any results for IgM Abs didn’t found in this study. Seventy – five samples studied in flowcytometry method which include twenty – five samples for each group. Diabetic patients with toxoplasmosisrecorded highest CD3 its mean 30.7± 14.51 pg /ml flowed by diabetic patients group has 24.84±9.47 pg /mland control group has 20.03± 9.42 pg /ml with significant differences.